Economic viability of wind microgenerators for single-family homes in the state of Piauí, Brazil - Teixeira de Albuquerque, Ytallo Rafaell; dos Santos, Luan (Latin American Journal of Energy Research, 2023)
: With the diversification of the Brazilian energy matrix and with the growing participation of wind energy in the generation of electric energy, Brazil advances to higher levels. In the fierce competition, the growing race for renewable sources, which causes a decrease in the accentuated dependence on fossil and hydraulic sources, thus enabling the generation of electricity from homes with low environmental impact. In this sense, this work aimed to present an analysis of economic viability in relation to the installation of a microgeneration system of electric energy derived from the wind potential that had as proposed area for study the locality of the state of Piaui, Brazil, for being characterized as a region with constant and good quality winds. Through a bibliographic survey on wind generation and economic engineering tools, an analysis was made of the economic impact and the return-on-investment time, as well as the cost-effectiveness of a wind installation in the studied region. Thus, the wind microgeneration system model applied was of the interconnected type, considering that the application of the model to the proposed area was economically unfeasible.
Keywords: Economic engineering; We, the undersigned, hereby transfer all copyrights of the manuscript entitled "BIOPHYSICAL MAPPING OF THE HUMAN IRIS: TECHNOLOGICAL ADVANCES AND APPLICATIONS IN DIAGNOSIS AND BIOMETRICS" to the Brazilian Journal of Health Research. We further declare that the manuscript is original and is not being considered for publication in another journal, in print or electronic format.; Rate of return; Renewable sources; access to healthcare; Wind energy